Impact of IT offerings strategies and IT integration capability on IT vendor value creation. Issue 6 (2nd November 2019) - Ceci, Federica; Masini, Andrea; Prencipe, Andrea
ABSTRACT: While IT integration is recognised as an important capability, the mechanisms through which it creates value and the contingencies that delimit its effectiveness are unclear – particularly, in the case of firms that deliver solutions embodying both products and services. We focus on IT vendors to investigate the effectiveness of IT integration capability with respect to three aspects of IT solution offerings: breadth, modularity and customisation. We find a complementarity effect between IT integration capability and management of the IT offer strategy: IT integration is fundamental regardless of whether the firm relies on customisation or a broad set of heterogeneous knowledge bases. However, when IT vendors adopt a modular design strategy, IT integration is made redundant and can be counterproductive.